PENGARUH FAKTOR EKSTERNAL DAN INTERNAL TERHADAP PROFITABILITAS BANK MUAMALAT INDONESIA - Rahmat Arsyad (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study is aim to test the effect of external and internal factor of Muamalat Bank. The external factor based on economics growth, and the internal factor is measured by CAR, BOPO and FDR of Return on Asset (ROA) of Muamalat Bank in Indonesia. This study use data from accounting report publiced by Muamalat Bank Indonesia and BPS report. The data analysis method is multiple linear regression. Before using this method the data must be test by clssic assumption test that are normality test and other test. Since observation periode, we goin the test data. Based on normality test, the data is distributed normal, and the classic assumption are fulfilled it means we can use multiple linear regression method. The study result shows that economics growth, CAR and FDR did not have significant effect to ROA, mean while BOPO have significant effect to ROA. Prediction capability for the four variabels to ROA in this study is about 99,2%, while the residual is effected by the other factor.